Message - Al-kaf, Prof. Dr. Ali Gamal (Universal Journal of Pharmaceutical Research, 2024)
In reality, UJPR is currently acknowledged as an international journal that is indexed in different locations. In the near future, I believe our journal will attain an impact factor and become a member of Scopus journals. With its highly experienced editorial board, excellent submissions, and excellent manuscript reviewers, UJPR will be able to advance and establish a solid reputation around the world. Using this as an occasion, I will urge all authors to ensure that their submissions are prepared in precise accordance with journal guidelines. This will help to prevent unwarranted delays in the editorial processing of their work and the disappointment of rejection. It's critical to know that you have access to the greatest resources and knowledge when your company depends on you for research support. Scopus provides extensive content coverage that links you to trustworthy, accurate research, enabling you to find the answers you need quickly. Strategic research decisions can be informed by using Scopus to measure research performance at the individual or institutional level. And because every title on Scopus is chosen by the impartial Content Selection & Advisory Board, you can be sure that you are giving your company the best possible data. More than 84% of the top 100 universities use Scopus, a data source that is widely accepted by prestigious institutions worldwide. Scopus is the source of data for the QS rankings and Times Higher Education. Finally, I hope that in upcoming yrs UJPR will be indexed with Scopus, we will continuously publish quality articles for which we invite additional original articles to be submitted and for you to cite relevant works published in this journal in your future publications.